2017
DOI: 10.1039/c7fo01183k
|View full text |Cite
|
Sign up to set email alerts
|

Impact of daily strawberry consumption on blood pressure and arterial stiffness in pre- and stage 1-hypertensive postmenopausal women: a randomized controlled trial

Abstract: Growing evidence indicates that strawberries are cardioprotective. We conducted an eight-week randomized, double-blind, placebo-controlled, parallel arm clinical trial to investigate the effects of daily consumption of freeze-dried strawberry powder (FDSP) on blood pressure (BP) and arterial stiffness in pre- and stage 1-hypertensive postmenopausal women. Sixty postmenopausal women were randomly assigned to one of three groups: (1) control, (2) 25 g FDSP and (3) 50 g FDSP (n = 20 per group). Assessments of bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 52 publications
1
33
0
Order By: Relevance
“…In agreement with responses observed in MetS subjects during the present investigation, Johnson et al (2017) reported 12 weeks MTCJ consumption had no significant effect on lipids.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In agreement with responses observed in MetS subjects during the present investigation, Johnson et al (2017) reported 12 weeks MTCJ consumption had no significant effect on lipids.…”
Section: Discussionsupporting
confidence: 93%
“…However, Johnson et al (2017) observed a trend for lower total cholesterol with MTCJ compared to PLA. This suggests lipids may be more sensitive to improvement at higher anthocyanin, secondary metabolite and phase II conjugate concentrations; through higher dosages and/or longer supplementation length.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…The biological and functional properties of strawberries have been studied in animal models (4) and extended to humans in a few epidemiological studies (7)(8)(9) . In the past decade, emerging interventional trials have been conducted to examine the health effects of strawberries in humans (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) . However, most of these trials had small sample sizes, which might have resulted in insufficient statistical power.…”
mentioning
confidence: 99%